Health Kiosks in Market: A qualitative study of factors influencing the transferability of the program to a target context in Kenya - O. Jarim; K. Lydia; M. Grace; M. Anselimo (PLoS ONE, 2025)
Public health kiosks can enhance access to healthcare in rural communities. To understand how to apply such an effective intervention and achieve results in another setting is key. This study explores the factors that influence the transferability of health kiosks in community markets in Kenya, with a focus on cardiovascular disease prevention and health promotion. The study was conducted in Vihiga and Nyeri counties, Kenya, between December 2023 and January 2024, among 64 participants. This qualitative exploratory study was nested in an implementation project dubbed Health Kiosks in Markets (HEKIMA). Six focus group discussions and sixteen in-depth interviews were conducted among purposively selected healthcare workers, market leaders, and policy actors. The conceptual framework, Population–intervention–environment–Transfer Model of Transferability (PIET‐T), guided the study design, data analysis, and identification of key themes. It also provided recommendations to optimize the program transfer. The successful transfer of a community-based health intervention to new settings depends on four key factors: its demonstrated effectiveness, compatibility with the local infrastructure, alignment with decision-makers’ priorities, and the level of institutional and stakeholder support. The findings provide valuable insights for guiding and informing the applicability of an intervention to other contexts. We demonstrate that active stakeholder participation should be encouraged.